2004
DOI: 10.1128/mcb.24.8.3552-3561.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of an hTERT Mutant Defective in Telomere Elongation by Fusion with hPot1

Abstract: The protein hPot1 shares homology with telomere-binding proteins in lower eukaryotes and associates with single-stranded telomeric DNA in vitro as well as colocalizing with telomere-binding proteins in vivo. We now show that hPot1 is coimmunoprecipitated with telomeric DNA and that stable expression of this protein in telomerase-positive cells results in telomere elongation, supporting the idea that hPot1 is a bona fide mammalian telomere-binding protein. We previously found that mutations in the N-terminal DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 42 publications
2
87
0
Order By: Relevance
“…Furthermore, these results show that the N-DAT domain in mTERT, which is 82% similar to the human DAT region, functions properly in human cells (2). The N-DAT domain has been proposed to mediate telomerase access to telomeric chromatin (3,4) or to contribute to interactions between telomerase and telomere DNA repeats (40,52). Instead, our data identify the C terminus as a critical regulatory domain controlling the ability of TERT to stabilize telomeres in cells and to extend replicative lifespan.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Furthermore, these results show that the N-DAT domain in mTERT, which is 82% similar to the human DAT region, functions properly in human cells (2). The N-DAT domain has been proposed to mediate telomerase access to telomeric chromatin (3,4) or to contribute to interactions between telomerase and telomere DNA repeats (40,52). Instead, our data identify the C terminus as a critical regulatory domain controlling the ability of TERT to stabilize telomeres in cells and to extend replicative lifespan.…”
Section: Discussionmentioning
confidence: 69%
“…These DAT (dissociates activities of telomerase) domains were proposed to be required for the recruitment of telomerase to telomeric chromatin (3,4). Other analyses of these TERT mutants found that the DAT mutants showed reduced processivity, principally on oligonucleotide primers matching the natural telomere sequence, indicating that the DAT regions contribute to interactions between TERT and its telomere substrate (40,52).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This last observation is likely reflective of a gain in the rate of cell cycle progression (see below as well as Figures 7a and b), cumulative over the 2-week period of CFU growth. (DN710), which did not have reverse transcriptase activity, we included the amino-terminal (NDAT92 and NDAT122) and carboxy-terminal (CDAT1127) DAT TERT mutants, which are catalytically active but cannot support telomere maintenance, due to telomere localization defects (Armbruster et al, 2001(Armbruster et al, , 2004Banik et al, 2002), as well as primer-template positioning dysfunctions (Lee et al, 2003). The DAT mutants were previously reported to retain the capacity to promote the non-canonical functions of TERT in chromatin remodeling and are therefore competent to promote DNA-damage repair, despite defects in their canonical TERT functions .…”
Section: Resultsmentioning
confidence: 99%
“…However, the short duration of gene expression achieved by these methods may not allow for sufficient telomere elongation to ensure adequate cell replicative potential for tissue engineering applications. In light of this consideration, one additional potential approach is the transient delivery of a highly processive mutant of telomerase that rapidly elongates telomeres in vitro (44).…”
Section: Figmentioning
confidence: 99%